The Epistemic Criterion: A Response to Michael Hand - Cooling, Trevor (Journal of beliefs and values, 2014)
This article is a response to Michael Hand’s critique in this issue of my response to his use of the epistemic criterion as the sole means for identifying whether or not an issue should be identified as controversial. I argue that he has misunderstood my intention in suggesting that I was seeking to replace the epistemic criterion. Rather my purpose was to challenge his over-confidence in the decisiveness of reason and to temper his use of the epistemic criterion by suggesting it needed to embrace ethical concerns.